(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
In the southern Aral Sea region Zoroastrian dakhma are known on the hill Chilpyk, which is situated on north-western spur of Sultanuizdagian ridge, on assuarian repository of Kuba-mount, near Caravan saray Meshekli, on dakhma Djumard butcher on the territory ancient necropolis of Mizdakkhan, on elevation Krantaw. There are also presented repositories, which is related with Zoroastrian temples and assuarian burial rites